2014
DOI: 10.5966/sctm.2012-0170
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Articular Injection of Human Meniscus Stem/Progenitor Cells Promotes Meniscus Regeneration and Ameliorates Osteoarthritis Through Stromal Cell-Derived Factor-1/CXCR4-Mediated Homing

Abstract: Meniscus injury is frequently encountered in clinical practice. Current surgical therapy involving partial or complete meniscectomy relieves pain in the short-term but often leads to osteoarthritis (OA) in the long-term. In this study, we report a new strategy of articular cartilage protection by intra-articular injection of novel human meniscus stem/progenitor cells (hMeSPCs). We found that hMeSPCs displayed both mesenchymal stem cell characteristics and high expression levels of collagen II. In the rat menis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
110
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 47 publications
5
110
0
1
Order By: Relevance
“…However, they only tested the expression of CD34, CD45, CD44, CD90, CD105, and CD166 in human meniscus stem cells by flow cytometer without testing other stem cell markers, such as SSEA4, Nanog, Strol-1, nucleostemin, and CD73 (Shen et al 2013(Shen et al , 2014. To our knowledge, there is no such a report on investigation of the characterizations of meniscusderived stem cells with both flow cytometer and immunostaining.…”
Section: Discussionmentioning
confidence: 95%
“…However, they only tested the expression of CD34, CD45, CD44, CD90, CD105, and CD166 in human meniscus stem cells by flow cytometer without testing other stem cell markers, such as SSEA4, Nanog, Strol-1, nucleostemin, and CD73 (Shen et al 2013(Shen et al , 2014. To our knowledge, there is no such a report on investigation of the characterizations of meniscusderived stem cells with both flow cytometer and immunostaining.…”
Section: Discussionmentioning
confidence: 95%
“…Several lines of evidence revealed that CXCL12a/CXCR4 axis-mediated recruitment of MSCs is pivotal in damaged tissue repair in other disease conditions 7,15e18 . A recent in vivo study showed that the intra-articular injection of meniscus stem/progenitor cells promotes cartilage regeneration and ameliorates OA through CXCL12a/CXCR4 axismediated progenitor cell homing 19 . It is not clear, however, whether this protective effect of CXCL12a/CXCR4 axis directly depends on just the recruitment of MPCs or an additional paracrine effect of CXCL12a on chondrogenic differentiation of MPCs as well.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, approaches using cell therapy with tissue engineering and biomaterials are increasing [42].…”
Section: Cell Sourcementioning
confidence: 99%